2020
DOI: 10.1126/sciadv.aaz9281
|View full text |Cite
|
Sign up to set email alerts
|

Superficial white matter imaging: Contrast mechanisms and whole-brain in vivo mapping

Abstract: Superficial white matter (SWM) contains the most cortico-cortical white matter connections in the human brain encompassing the short U-shaped association fibers. Despite its importance for brain connectivity, very little is known about SWM in humans, mainly due to the lack of noninvasive imaging methods. Here, we lay the groundwork for systematic in vivo SWM mapping using ultrahigh resolution 7 T magnetic resonance imaging. Using biophysical modeling informed by quantitative ion beam microscopy on postmortem b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 44 publications
2
89
0
Order By: Relevance
“…Specifically and consistently with prior studies [46, 63], we found that FA values increased in sWM. In contrast to deep WM that plays an important role in subcortical and remote cortical connectivity, sWM is strongly influenced by cortical GM, particularly short cortical association fibers (also called arcuate or “U”-fibers), which connect adjacent gyri and comprise the majority of corticocortical WM connections [15]. FA increases in sWM might thus indicate stronger influence from axonal packing organization and myelination on short corticocortical WM connections.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically and consistently with prior studies [46, 63], we found that FA values increased in sWM. In contrast to deep WM that plays an important role in subcortical and remote cortical connectivity, sWM is strongly influenced by cortical GM, particularly short cortical association fibers (also called arcuate or “U”-fibers), which connect adjacent gyri and comprise the majority of corticocortical WM connections [15]. FA increases in sWM might thus indicate stronger influence from axonal packing organization and myelination on short corticocortical WM connections.…”
Section: Discussionmentioning
confidence: 99%
“…These quantitative parameters contain specific and complementary information regarding the microstructural properties of brain tissue, such as the extent of myelination, iron and water concentration (e.g. Weiskopf et al, 2015; Kirilina et al, 2020). Combining diffusion MRI with MPM thus allows for the examination of microstructural information related to the neuronal conduction velocity in the form of the axonal g-ratio (Mohammadi et al, 2015a; Mohammadi and Callaghan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…8,9 SWM mainly consists of short, thin, U-fibres linking nearby gyri that lie up to 2mm below the cortex but may represent 57-67% of all WM fibres. [10][11][12] SWM fibre organisation is also highly complex 13,14 and may form sub-networks of its own. 15 Unique anatomical, developmental and cellular SWM properties may lead to particular vulnerabilities to Alzheimer's disease-related pathology.…”
Section: Introductionmentioning
confidence: 99%